Utilization of Nanogels Binahong Leaf Extract on Palatal Wound Healing - Lestari, Chandra; Ilyas, Syafruddin; Hanafiah, Olivia Avriyanti (Archives of The Medicine and Case Reports, 2024)
The palatal wound is challenging to cure due to eating and chewing activities; hence, a medication delivery system is required to expedite the healing process. The leaf of the binahong plant contains saponins, tannins, alkaloids, flavonoids, and vitamin C. Binahong leaves contain important antibacterial, antiviral, anti-inflammatory, analgesic, and antioxidant properties. However, further discussion is necessary regarding the use of nanogels and binahong leaf extract in biomedical and pharmaceutical applications. Analyzing the effectiveness of nanogels binahong leaves in healing palatal mucosa wounds has been examined in previous research. Multiple studies have revealed that using nanogels and binahong leaf extract can accelerate wound healing on the skin and within the oral cavity by boosting fibroblasts, collagen, and other factors. In conclusion, the use of nanogel binahong leaf extracts has the ability to accelerate the healing of palatal mucosa wounds.